ANALISIS RASIO LIKUIDITAS, AKTIVITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Dewi, Eva Maulina; Ompusunggu, Hermaya (LPPM Universitas Putera Batam, 2021)
The main goal of every investor to invest should be to get a return on the invested capital, for this purpose, investors should see the financial performance of the company before investing. The main purpose of this research is to determine whether the financial performance measured by net profit is affected by the current ratio variable, the total asset turnover ratio, the debt / asset ratio and the return on equity. The population in this study consists of 10 manufacturing companies in the pharmaceutical subsector. This study uses purposeful sampling technique to determine which sample to take, and there are 8 companies sampled because they meet the specified sampling criteria. Data collection techniques using documentation techniques. The results of the hypothesis test using the t test show that the current ratio does not have a positive effect on net profit at the t number <t table 0.375 <2.0422 and a significant 0.710> 0.05 level, the total asset turnover ratio is positive. net profit t> t table 2.248> 2.0422 and a significant level 0.031 <0.05, debt / asset ratio - t number <- t has no positive effect on net profit, i.e. - 1.536 <- 2.0422 and 0.134> 0.05 a significant level at the level of return on equity, t number> t table 2.109> 2.0422 and significant 0.042 <0.05 have a positive effect on net profit. The results of the hypothesis test using the F test, current ratio, total asset turnover ratio, debt / asset ratio and net profit at the same time of return on equity, 3.292> 2.69 with the table t> t and a significant 0.022 <0.05.